Urgensi Musyawarah-mufakat dalam Pemenuhan Hak dan Informasi Publik, Melihat Fenomena dari Sudut Pandang Demokrasi Deliberatif Jurgen Habermas - Alif Firdaus Zam Zam; Midkholus Surur; Halimur Rosyid; Mahmud Aprian Mabruri; Nanda N. Azzahra (Universitas Islam Darul Ulum Lamongan, 2023)
This article tries to reveal community culture again through deliberation and consensus in public spaces which are starting to be displaced by virtual spaces. This loss of public space culture has an impact on the failure to fulfill basic citizen rights, namely the right to know public information. Jurgen Habermas' deliberative democracy opens up discussion and context efforts in the public space to educate the public so that they have access to information on issues of common life. Activities through this process can not only be a reference in forming joint policies, but can also be a training for the public to think rationally.